Venom variation during prey capture by the cone snail, Conus textile. - Cecilia A Prator; Kellee M Murayama; Joseph R Schulz (PLoS ONE, 2014)
Observations of the mollusc-hunting cone snail Conus textile during feeding reveal that prey are often stung multiple times in succession. While studies on the venom peptides injected by fish-hunting cone snails have become common, these approaches have not been widely applied to the analysis of the injected venoms from mollusc-hunters. We have successfully obtained multiple injected venom samples from C. textile individuals, allowing us to investigate venom compositional variation during prey capture. Our studies indicate that C. textile individuals alter the composition of prey-injected venom peptides during single feeding events. The qualitative results obtained by MALDI-ToF mass spectrometry are mirrored by quantitative changes in venom composition observed by reverse-phase high performance liquid chromatography. While it is unclear why mollusc-hunting cone snails inject prey multiple times prior to engulfment, our study establishes for the first time a link between this behavior and compositional changes of the venom during prey capture. Changes in venom composition during hunting may represent a multi-step strategy utilized by these venomous animals to slow and incapacitate prey prior to engulfment.